2021
DOI: 10.3389/fmolb.2021.638396
|View full text |Cite
|
Sign up to set email alerts
|

MD Simulations on a Well-Built Docking Model Reveal Fine Mechanical Stability and Force-Dependent Dissociation of Mac-1/GPIbα Complex

Abstract: Interaction of leukocyte integrin macrophage-1 antigen (Mac-1) to platelet glycoprotein Ibα (GPIbα) is critical for platelet–leukocyte crosstalk in hemostasis and inflammatory responses to vessel injuries under hemodynamic environments. The mechano-regulation and its molecular basis for binding of Mac-1 to GPIbα remain unclear, mainly coming from the lack of crystal structure of the Mac-1/GPIbα complex. We herein built a Mac-1/GPIbα complex model through a novel computer strategy, which included a flexible mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…However, there might be a significant gap between the results from the MD simulation and the data measured with single molecular tools, such as atomic force microscopy (AFM), optical and magnetic tweezers [ 29 ], coming from effects of timescale on predicting ligand–receptor interactions with a timescale of about 0.01–1.00 s by MD simulation of about 100 ns. Regardless of the timescale effect on complex dissociation , it was expected here that , the mechano-regulation factor or the normalized complex dissociation probability, should be comparable with experimental data if the conformations sampled from the simulation are perfect [ 22 , 24 ].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, there might be a significant gap between the results from the MD simulation and the data measured with single molecular tools, such as atomic force microscopy (AFM), optical and magnetic tweezers [ 29 ], coming from effects of timescale on predicting ligand–receptor interactions with a timescale of about 0.01–1.00 s by MD simulation of about 100 ns. Regardless of the timescale effect on complex dissociation , it was expected here that , the mechano-regulation factor or the normalized complex dissociation probability, should be comparable with experimental data if the conformations sampled from the simulation are perfect [ 22 , 24 ].…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, the mechanical force also plays a crucial role in the growth and metastasis of tumor cells [ 13 ]. The mechano-sensitive proteins, such as integrins, selectins, and other transmembrane receptors/ligands, have been reported to have the force-induced changes of conformations and functions [ 18 , 19 , 20 , 21 ]; these changes will enhance or reduce subsequent transmembrane signaling, cell–cell interactions, and cellular biological processes [ 19 , 22 , 23 ]. It hints that a force-dependent interaction between DNAM-1 and CD155 may be required in mediating the involved cellular events in mechano-microenvironment, such as substrate rigidity, blood vessel extension, blood flow shear force, and so on [ 19 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we found that the stretched complex was stable under the given tensile force of 25 pN, and the force would enhance binding of CD172a to CD47 with or without PTM, but the complex with PTM had better mechanical stability in comparison with one without PTM ( Figure 5 C). This catch–bond phenomenon might be required for a stable cell–cell crosstalk, has been observed in various molecular systems, including P-selectin bound with PSGL-1 using the force clamp assay with AFM and a flow chamber [ 38 ], as well as Kindlin2 bound with β3 integrin and Mac-1 bound with GPIbα using molecular dynamics simulations [ 39 , 40 ]. So, the aforementioned data from SMD simulations stated that CD47 was mechano-sensitive, had a stable tension-induced allostery with an enhanced affinity to CD172a, and served not only linker molecules but also as a mechano-chemical signaling axis in cell–cell cross talking through binding with CD172a, while PTM raised the mechanical strength of the CD47-CD172a axis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhang et al demonstrated a catch-slip bond transition at a force threshold in the interaction between β 3 integrin and Kindlin2 [79]. Furthermore, a catch-slip bond transition of the interaction between leukocyte integrin macrophage-1 antigen (Mac-1) and platelet glycoprotein Ibα (GPIbα) was predicted through the dissociation probability, which provides insights into the platelet-leukocyte interactions during hemostasis and inflammatory responses under mechanical stress [80]. Interestingly, molecules of the same kind but with different conformations may respond differently to tensile stress.…”
Section: Tensionmentioning
confidence: 99%